ChemInform Abstract: Synthesis and Crystal Structure of Rutile‐Type ScTa2O5N. Issue 3 (January 2015) - Cosgun, Sevilay; Rohloff, Martin; Goebel, Caren; Gernert, Ulrich; Fischer, Anna; Lerch, Martin
Abstract The title compound is prepared by oxidizing ammonolysis of an amorphous Sc‐Ta‐O precursor derived by Pechini‐type sol‐gel processing (800 °, 2 h, NH3 and O2 flow rates of 10 and 0.1 l/h, resp., phase purity of 90%).